Information and psychological safety principles of students receiving higher education - Куцак, Алла Валеріївна; Kutsak, A. V. (Минск : БГУ, 2020)
The article discusses the features of the informatization process influence on student’s personality. The use of information technologies in the educational process has been analyzed through the prism of their positive and negative impact on students. The focus is on manipulating the minds of students through the Internet and social networks. As a means of ensuring the informational and psychological safety of subjects of educational activities, it is proposed to form rational methods of perception, memorizing and interpreting information, and develop criteria for assessing its quality and usefulness.
Keywords: students; information and psychological security; personal values; achievement motivation